Two parameters weibull analysis on mechanical properties of kenaf fiber under various conditions of alkali treatment - Hashim, Mohd Yussni; Mohd Amin, Azriszul; Marwah, Omar Mohd Faizan; Othman, Mohd Hilmi; Hanizan, Nurnajwa Hani; Norman, Mohd Khairul Efni (UTHM Publishing, 2020)
This paper present two parameters Weibull analysis result on mechanical properties of kenaf fiber under different condition of alkali treatment. The mechanical properties of kenaf fiber that as focused in this study was fiber matrix interfacial shear strength (IFSS) and fiber tensile strength (TS). Kenaf fiber were treated under various conditions alkali concentration at 2, 6 and 10 (w/v%), immersion duration at 30, 240 and 480 minute and immersion temperature at 27, 60 and 100oC. Unsaturated polyester matrix was used in this study to determine the interfacial shear strength (IFSS). The result shows that Weibull modulus of kenaf fiber interfacial shear strength (IFSS) at 30 minutes immersion duration value was 2.59 to 3.12 with characteristic strength, σo-IFSS value range was 0.29MPa to 0.37MPa. The highest Weibull modulus was at room temperature and 6% alkali concentration. For kenaf fiber tensile strength Weibull modulus, the range was 2.40 to 3.07 with characteristic strength value range from 345MPa to 597MPa. The highest Weibull modulus also was measured at room temperature and 2% alkali concentration. The characteristic strength value shows a degrading pattern with the increment on immersion temperature and alkali solution concentration.